Perioperative Automated Noninvasive Blood Pressure- (NIBP-) Related Peripheral Nerve Injuries: An Anesthetist’s Dilemma—A Case Report and Review of the Literature - Waleed Elmatite; Chanchal Mangla; Surjya Upadhyay; Joel Yarmush (Case Reports in Anesthesiology)
Peripheral nerve injury following regional or general anesthesia is a relatively uncommon entity but, potentially, a serious complication of anesthesia. Most nerve injuries are related to either regional anesthesia or position-related complications, and they are rarely seen in association with the use of automated blood pressure monitoring. We describe a patient who developed neurological dysfunction of all the three major nerves, median, ulnar, and radial, after general anesthesia. The distribution of sensory motor deficit along with the nerve conduction study demonstrated the location of the anatomical nerve lesions coinciding with the automatic noninvasive blood pressure (NIBP) cuff. No other cause of nerve injury was identified except for the use of the NIBP cuff. In the absence of another identifiable cause, we strongly suspected the NIBP cuff compression as a possible cause for the nerve injuries. In this article, we will discuss the possible risk factors, mechanisms, diagnosis, and prevention of perioperative nerve injury.